1998
DOI: 10.1063/1.56976
|View full text |Cite
|
Sign up to set email alerts
|

Light collection from scintillation counters using WLS fibers and bars

Abstract: Abstract. Several methods of collecting light on scintillation counters using WLS fibers and WLS bars were studied. Nearly 20 prototype counters with different designs and with sizes ranging from 14×11×1.3cm 3 to 105×60×1.3cm 3 have been tested using cosmic muons and radioactive source. The efficiency of light collection on number of photoelectrons, uniformity of response, and time resolution have been measured. Test results for two new designs of light collection from scintillator based on WLS fibers around p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 2 publications
2
10
0
Order By: Relevance
“…The counters are made from Bicron 404A scintillator with G2 fiber embedded in vertical grooves [92] in a manner similar to the cosmic bottom counters described above. The grooves are about 1.75" apart and run along the length of each counter from the edge to the middle.…”
Section: Aφ Scintillation Countersmentioning
confidence: 99%
See 1 more Smart Citation
“…The counters are made from Bicron 404A scintillator with G2 fiber embedded in vertical grooves [92] in a manner similar to the cosmic bottom counters described above. The grooves are about 1.75" apart and run along the length of each counter from the edge to the middle.…”
Section: Aφ Scintillation Countersmentioning
confidence: 99%
“…The unpolished sides result in a larger number of photoelectrons and better uniformity than polished sides do and cost less [92]. The scintillator and WLS bars are wrapped in Tyvek for better light collection and black paper for light tightness.…”
Section: Trigger Scintillation Countersmentioning
confidence: 99%
“…From measurements [15], we concluded that for the geometry of our counters, WLS bars give better light collection efficiency and allow a simpler construction procedure than WLS fibers. The design using WLS bars for light collection was chosen as the basic option for the large majority of the counters [18].…”
Section: Pixel Counter Design and Mountingmentioning
confidence: 99%
“…All four sides of the trapezoidal scintillator plate are machined but not polished. Our studies concluded that the less expensive unpolished design has better photoelectron yield and uniformity [15,18]. Two WLS bars, 4.2 mm thick and 12.7 mm wide, are placed along two edges of the scintillator plate with air gaps provided by narrow strips of adhesive tape attached to the scintillator plate as spacers.…”
Section: Pixel Counter Design and Mountingmentioning
confidence: 99%
See 1 more Smart Citation